Alternatives to rethink tomorrow: Biodiesel production from residual and non-edible oils using biocatalyst technology - Ferrero, Gabriel Orlando (2019)
Esterification and/or transesterification of a residue from soybean oil obtaining process, Jatropha hieronymi oil (non-edible), waste frying oil (sunflower) and commercial sunflower oil were studied for biodiesel production. Enzyme lipase of Pseudomonas fluorescens immobilized on sodium-modified-SBA-15 was employed as biocatalyst. The experiments were carried out in a batch reactor taking samples at different times and determining the biodiesel production by HPLC. The biocatalyst was able to produce biodiesel from residual or undervalued oils (without any previous refinement) and commercial ethanol as co-substrate. The advantage of the latter is the possibility of obtaining ethanol from a fermentative process, which favors a sustainable development. Biodiesel yields between 70 and 95% were achieved depending on the employed oil.